(untitled) (Advancements in Homeopathic Research, 2022)
The concept of monogram was presented in ‘Absolute Homeopathic MM’, written by Dr. P.I. Tarkas and Dr. Ajit Kulkarni and published by B. Jain Publishers, New Delhi. Dr. Ajit Kulkarni deals with the evolution of Materia Medica, keynotes, key themes etc. and then explain the concept of Materia Medica with philosophy, abstraction and generalization, correlation with data in MM and case illustration and meaning of words coined for monogram.